2010
DOI: 10.1007/978-3-642-15420-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Clustering in a Multi-Agent Data Mining Environment

Abstract: Abstract. A Multi-Agent based approach to clustering using a generic Multi-Agent Data Mining (MADM) framework is described. The process use a collection of agents, running several different clustering algorithms, to determine a "best" cluster configuration. The issue of determining the most appropriate configuration is a challenging one, and is addressed in this paper by considering two metrics, total Within Group Average Distance (WGAD) to determine cluster cohesion, and total Between Group Distance (BGD) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…These findings are currently being incorporated into a MAS framework [6,7]. The techniques investigated sofar, and reported here, do not serve to find the best results in all cases and further investigation is therefore required, however the authors are greatly encouraged by the result reported in this paper.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…These findings are currently being incorporated into a MAS framework [6,7]. The techniques investigated sofar, and reported here, do not serve to find the best results in all cases and further investigation is therefore required, however the authors are greatly encouraged by the result reported in this paper.…”
mentioning
confidence: 85%
“…The process was incorporated into a MAC framework founded on earlier work by the authors and reported in [6,7]. An issue with K-means is that the initial points (records/objects) used to define the initial centroids of the clusters are randomly selected.…”
Section: Parameter Identification For Clustering Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases the algorithms do not have enough detail that allows them to be reverse engineered, and contact with their authors did not resolve the issue. References used in tables (4.4, 4.5) are as follows, (1) = [Handl et al, 2003a], (2) = [Tan et al, 2011], (3) = [Boryczka, 2010], (4) = , (5) = [Martens et al, 2007], (6) = [Xiong et al, 2012], (7) = [Chaimontree et al, 2010], (8) = [Breaban and Luchian, 2011], (9) = [Monmarché et al, 1999a], (10) = [Niknam and Amiri, 2010], (11) = [Santos and Bazzan, 2009], (12) = [Chandrasekar and Srinivasan, 2007], (13) = [Cano et al, 2013], (14) = [Wan et al, 2012], (15) = [Tan et al, 2006], (16) = [Bougenière et al, 2009], (17) = [Wang et al, 2007], (18) = [Jebara, 2002], (19) = [Rami and Panchal, 2012], (20) = [Azzag et al, 2007], (21) = [Labroche et al, 2002a], (22) = [Guo et al, 2003], (23) = [Yang and Zhang, 2007], (24) = [Ingaramo et al, 2005], (25) = [Shukran et al, 2011].…”
Section: Evaluating the Mpaca Clustering Performancementioning
confidence: 99%